Using Content Analysis in LIS Research: Experiences with Coding Schemes Construction and Reliability Measures - Lin, Chi-Shiou; Jeng, Wei (Qualitative and Quantitative Methods in Libraries, 2017)
Content analysis is now also popular in LIS research. It is a flexible and unobtrusive method to analyse the meanings of narratives objectively. However, the objectivity of analysis relies heavily on a well-constructed coding scheme as well as the consistency of coding behaviour. In this paper, we shared our experiences with content analysis in three very different LIS research. We emphasized on the development of mutual exclusive and comparable coding schemes in each study in order to enhance the internal validity and extensibility for future research. We also discussed on the reliability considerations. Hopefully it may encourage more discussion on the methodology and contribute to the vigour of the content analysis based investigations.